1818 Vt. Acts & Resolves 64-65, An Act Regulating and Governing the Militia of This State, § 42. - (:unkn) unknown (General Publisher, 1818)
No noncommissioned officer, private or citizen shall unnecessarily fire a gun, single musket or pistol, in any public road, or near any house or place of parade, on the evening preceding, on the day or evening of the same, on which any troop company, battalion or regiment shall be ordered to assemble for military duty
--
Keywords: DISCHARGE